Esterilización de limas endodónticas mediante agentes químicos. Universidad Nacional de Chimborazo, 2018 - Unach (2019)
The purpose of this research was to check the in vitro efficacy of chemical agents for the sterilization of endodontic files used in the clinics of the National University of Chimborazo. It used 21 samples of contaminated endodontic files after performing the instrumentation of the root canal system of the tooth, It was divided into three groups: the group one corresponded to the sterilization group in autoclave, group two was sterilized in glutaraldehyde at 2% in times of 6, 12, and 24 hours and group three was sterilized with formalin tablets at 95% at 6, 12, 24 hours. The results obtained in the investigation with the statistical method of U Mann Whitney determined that there are no significant statistical differences between the values of glutaraldehyde to 2% and the formalin tablets to 95% of samples that were sterilized, so the two chemical agents have the same ability to sterilize. By means of the Wilcoxon statistical method It is concluded that the best chemical agent for the sterilization of endodontic files was the formalin tablets at 95% with a time of 24 hours in which a sterilization is produced at 100%.